FRI0242 Watermelon stomach in systemic sclerosis: A EUSTAR case-control study. (23rd January 2014) - Ghrenassia, E.; Avouac, J.; Derk, C.; Airo, P.; Khanna, D.; Berezne, A.; Tiev, K.; Ingegnoli, F.; Rosato, E.; Caramaschi, P.; Hesselstrand, R.; Riccieri, V.; et al.
Abstract : Background: Watermelon stomach (WS) or Gastric Antral Vascular Ectasia (GAVE) is a very rare gastric complication of Systemic Sclerosis (SSc). It has a unique endoscopic appearance that is characterized by multiple longitudinal stripes of red vessels, which radiate in a spoke-like fashion from the pylorus to the antrum. The characteristics of patients with SSc-GAVE remain poorly described. Objectives: The aim of this study was to determine the subgroup at risk together with the outcomes of SSc patients with GAVE. Methods: We performed a retrospective, multicenter, international, case/control study. We collected cases of SSc-GAVE cases through EUSTAR network. Every case was matched with 2 SSc controls recruited from the same center, matched for age, sex, cutaneous subtype and disease duration. Disease characteristics were recorded at the time of GAVE occurrence and the last observation was used to defined the outcomes. Results: We included 29 cases of SSc patients with GAVE, who were compared to 58 SSc controls. These 29 SSc patients (26 women, 89%) had a mean ± standard deviation (SD) age of 59±13 years and a mean ± SD disease duration of 7±3 years; 17 (59%) had the diffuse cutaneous subset and 12 (41%) the limited. Among these patients, 28 (97%) had anaemia, 13 (45%) needed red blood cell transfusion, and 18 (62%) required endoscopic treatment. In addition, SSc patients with GAVE were more likely to have positive anti-RNA polymerase-III antibodies (17/29, 60% vs. 8/58, 14%, p=0.0002), DLCO/AV<75% predicted (18/29, 61% vs. 14/58, 24%, p=0.005), and decreased frequency of anti-topoisomerase-I antibodies (1/29, 3% vs. 21/58, 36%, p=0.02) and pulmonary fibrosis (7/29, 24% vs. 33/58, 58%, p=0.007) compared to SSc patients without GAVE. The likelihood of other SSc-related disease characteristics were not different between cases and controls. Multivariate analysis including disease characteristics with a univariate P-value≤0.1 confirmed positive anti-RNA polymerase-III antibodies as an independent factor associated with GAVE (odds ratio: 5.76, 95% confidence interval 1.29-25.64, p=0.02). After a follow-up of 35±27 months, 7/29 (24%) had a relapse of bleeding requiring new local endoscopic treatment. Among these 7 patients, 5 needed red blood cell transfusion. Conclusions: Presence of antibodies to RNA-Polymerase-III antibodies may be useful to identify the subset of SSc patients with increased risk for GAVE. Despite it was described as a late complication, SSc patients with GAVE had early disease duration in our cohort. GAVE appears as a cause of anaemia that clinicians should be aware of. This complication often requires local endoscopic therapy, which is usually efficient, despite frequent recurrent events. The inclusion of further cases in this ongoing project may help to better characterise the features of this rare complication. Disclosure of Interest: None Declared